From Isolated Emotional Memories to Their Competition During Conflict - Bravo-Rivera, Christian; Sotres-Bayon, Francisco (Frontiers in Behavioral Neuroscience, 2020)
Aversive or rewarding experiences are remembered better than those of lesser survival significance. These emotional memories, whether negative or positive, leave traces in the brain which can later be retrieved and strongly influence how we perceive, how we form associations with environmental stimuli and, ultimately, guide our decision-making. In this review, we outline what constitutes an emotional memory by focusing on threat- and reward-related memories and describe how they are formed in the brain during learning and reformed during retrieval. Finally, we discuss how the field is moving from understanding emotional memory brain circuits separately, towards studying how these two opposing brain systems interact to guide choices during conflict. Here, we outline two novel tasks in rodents that model opposing binary choices (approach or avoid) guided by competing emotional memories. The prefrontal cortex is a major integration hub of emotional information which is also known to be critical for decision-making. Consequently, brain circuits that involve this brain region may be key for understanding how retrieval of emotional memories flexibly orchestrates adaptive choice behavior. Because several mental disorders (e.g. drug addiction and depression) are characterized by deficits in decision-making in the face of conflicting emotional memories (maladaptively giving more weight to one memory over the other), the development of choice-based animal models for emotional regulation could give rise to new approaches for the treatment of these disorders in humans.